(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This study holds practical significance as it delves into the psychological challenges faced by individuals preparing for marriage, a critical phase that sets the tone for their future relationship. By focusing on the pre-marital stage, the study aims to address issues that could impact the success of the marital union. This study Aims to identify psychological issues faced by soon-to-be-married individuals and provide necessary support and counseling, assess the level of psychological health among soon-to-be-married individuals, and to evaluate attitudes towards marriage expectations and forms (early, late, and multiple). The study holds theoretical importance by addressing the rising divorce rates among marriage applicants and contributing to the body of research on marital life. Additionally, it fills a gap in existing research on mental health and attitudes towards marriage specifically in Taif governorate. The results of study concluded the males exhibit a more favorable attitude towards marriage compared to females, Individuals aged 20-25 display the most positive attitudes towards marriage, Undergraduate individuals show better attitudes towards marriage compared to other educational levels, males demonstrate better mental health compared to females, individuals under 20 years old show better mental health compared to other age groups, undergraduate individuals exhibit better mental health compared to other educational levels.